Perkembangan Term Jihad Dalam Al-Qur’an: Aplikasi Pendekatan Semantik Toshihiko Izutsu - Anita Azizah; Muhammad Mundzir (QOF, 2022)
This paper aimed to explore the development of the meaning of the term jihad in the Qur'an using Toshihiko Izutsu's semantic approach, namely looking for basic meaning, relational meaning, and giving rise to a concept. This research included library research by collecting data on the term jihad in the verses of the Qur'an. The analysis of the verses was done using linguistic analysis. The results showed that the term jihad is not only understood with something radical, but can be understood as a form of earnestness in goodness with the conditions being faced either individually or in groups, with the form of deeds, speech, property, and thoughts. This research also proved that there is a context of jihad outside of war, such as jihad against lust, jihad against evil, jihad in the family, jihad in property, and jihad of knowledge or against ignorance. Synonyms of the term jihad in the Qur'an include: using the terms kadaḥa and naṣaba which mean hard work, earnestness. That way, jihad can be used in all aspects of life such as jihad in the education, government, economy and trade sectors.